The application of Temporary Ark Hospitals in controlling COVID‐19 spread: The experiences of one Temporary Ark Hospital, Wuhan, China. Issue 10 (29th June 2020) - Yuan, Yan; Qiu, Tao; Wang, Tianyu; Zhou, Jiangqiao; Ma, Yonggang; Liu, Xiuheng; Deng, Hongping
Abstract: Coronavirus disease 2019 (COVID‐19) had its evolution in Wuhan, Hubei Province, China, and now it has spread around the world, resulting in a large number of deaths. Temporary Ark hospitals (TAHs) have played an important role in controlling the spread of the epidemic in the city of Wuhan. Taking one TAH with 800 beds as an example, we summarized details of the layout, setting, working mode of medical staff, patient management, admission standards, discharge standards, and standards for transferring to another hospital, hospital operation, and so on. Over the period of operation, a total of 1124 patients were admitted for treatment. Of these, 833 patients were cured and discharged from the hospital and 291 patients were transferred to other designated hospitals, owing to aggravation of their condition. The achievement was to have zero infection for medical staff, zero in‐hospital deaths among admitted patients, and zero readmission for discharged patients. The rapid deployment of TAH provided a suitable place for treating mild/moderate or no asymptomatic COVID‐19 patients, which successfully helped to control the infection in Wuhan. The successful model of TAH would rapidly and effectively control the spread of COVID‐19 in other cities. Highlights: Temporary Ark hospitals (TAHs) have played an important role in controlling the spread of the epidemic in the city of Wuhan. We described in detail how one TAH works. Zero infection for medical staff, zero in‐hospital deaths among admitted patients, and zero readmission for discharged patients in our TAH. The successful model of TAH would rapidly and effectively control the spread of COVID‐19 in other cities.